Liver-fibrosis-activated transcriptional networks govern hepatocyte reprogramming and intra-hepatic communication - Loft, Anne; Alfaro Nunez, Ana Jimena; Schmidt, Søren Fisker; Pedersen, Felix Boel; Terkelsen, Mike Krogh; Puglia, Michele; Chow, Kan Kau; Feuchtinger, Annette; Troullinaki, Maria; Maida, Adriano; Wolff, Gretchen; Sakurai, Minako; et al. (Cell metabolism, 2021)
Liver fibrosis is a strong predictor of long-term mortality in individuals with metabolic-associated fatty liver disease; yet, the mechanisms underlying the progression from the comparatively benign fatty liver state to advanced non-alcoholic steatohepatitis (NASH) and liver fibrosis are incompletely understood. Using cell-type-resolved genomics, we show that comprehensive alterations in hepatocyte genomic and transcriptional settings during NASH progression, led to a loss of hepatocyte identity. The hepatocyte reprogramming was under tight cooperative control of a network of fibrosis-activated transcription factors, as exemplified by the transcription factor Elf-3 (ELF3) and zinc finger protein GLIS2 (GLIS2). Indeed, ELF3- and GLIS2-controlled fibrosis-dependent hepatokine genes targeting disease-associated hepatic stellate cell gene programs. Thus, interconnected transcription factor networks not only promoted hepatocyte dysfunction but also directed the intra-hepatic crosstalk necessary for NASH and fibrosis progression, implying that molecular “hub-centered” targeting strategies are superior to existing mono-target approaches as currently used in NASH therapy.
Gesehen am 15.07.2021